Tissue-specific expression and functional role of keratin 1 in sheep horn development - Mei, Qiao; Li, Hao; Zhang, Guoqing; Meng, Zhu; Zhang, Shiwen; Liu, Fei; Pan, Zhangyuan; Yang, Jie (Frontiers in Veterinary Science, 2025)
IntroductionSheep horn development has significant implications for animal welfare and farm management, yet its molecular mechanisms remain incompletely understood. Keratin 1 (KRT1), a key structural protein in epidermal keratinization, has been implicated in horn formation. This study systematically investigates the expression patterns, genetic variations, and functional role of KRT1 in sheep horn development.MethodsWe integrated RNA sequencing (RNA-seq) and whole-genome sequencing (WGS) data from Tibetan sheep and public databases. Multi-tissue expression profiling of KRT1 was performed across sheep, cattle, pigs, and humans. Phylogenetic and protein structural analyses identified conserved amino acid sites. Allele-specific expression (ASE) loci and functional SNPs were screened using population genetics approaches. Association analysis linked genotypes with horn length in Small Tail Han sheep.ResultsKRT1 expression was significantly higher in scurred (small-horned) sheep compared to SHE (large-horned) sheep (p = 0.024), and exhibited tissue-specific enrichment in horn, skin, and periosteum. Cross-species analysis confirmed high KRT1 expression in horn and skin tissues. We identified 11 horned-artiodactyl-specific amino acid sites, including K312, which forms a hydrogen bond with E262 of KRT10; mutations at this site disrupted the interaction. Four ASE loci showed strong bias toward reference alleles in horned phenotypes. Thirty-two functional SNPs were prioritized, and nine haplotype blocks contained 13 highly differentiated SNPs (Fst > 0.05). Four SNPs were significantly associated with horn length, with wild-type homozygotes exhibiting longer horns (p < 0.05).DiscussionOur findings demonstrate that KRT1 plays a critical role in sheep horn development through its expression regulation, protein interaction stability, and genetic variation. The conserved K312 residue and associated SNPs may serve as potential molecular markers for horn phenotype selection. These results provide new insights into the keratin-based mechanisms underlying horn morphogenesis and offer a foundation for molecular breeding strategies aimed at horn size and type modulation in sheep.